Redox regulation of glutamate-1-semialdehyde aminotransferase modulates the synthesis of 5-aminolevulinic acid in Arabidopsis - Sinha, Neha; Hussein, Rana; Paul, Jerome; Nazare, Marc; Grimm, Bernhard (Frontiers in Plant Science, 2025)
Plants are constantly exposed to sudden changes in environmental parameters and must respond quickly to changes in temperature, humidity and light conditions. Such fluctuations in growth conditions also require almost immediate adjustments in the synthesis of photosynthetic pigments. Post-translational redox control of tetrapyrrole metabolism for chlorophyll and heme synthesis provides the necessary modifications for photosynthesis. The enzyme glutamate-1-semialdehyde aminotransferase (GSAAT) contributes to the rate-limiting step in the synthesis of 5-aminolevulinic acid (ALA). We intend to specifically investigate the redox control of GSAAT, analyze the redox-dependent shifts in the thiol-disulphide state of GSAAT, and identify the redox-dependent cysteines responsible for changes in the structure, enzymatic activity and stability of the protein. Wild-type GSAAT and Cys→Ser substitution mutants of the enzyme were examined for their activities with the labile substrate of GSAAT, glutamate-1-semialdehyde, which was synthesized in a simplified manner using a novel method. We show that of the four cysteine residues found in GSAAT, Cys168 and Cys190 are crucial for the redox-regulated state of GSAAT. Based on these experiments, we propose a redox-dependent structural modification of GSAAT that could lead to a decrease in the activity of the oxidized protein compared to the reduced enzyme.